Targeting the ATP synthase in bacterial and fungal pathogens: beyond Mycobacterium tuberculosis - Martin Vestergaard; Dirk Bald; Hanne Ingmer (Journal of Global Antimicrobial Resistance, 2022)
ABSTRACT: The ATP synthase is a multicomponent enzyme that is largely conserved across the kingdoms of life. In many species the ATP synthase is central in the synthesis of ATP by using the electrochemical proton gradient generated via the electron transport chain. Bacteria inhabit very diverse ecological niches; hence their metabolism to extract nutrients and generation of ATP varies from species to species. Some species are obligate aerobes (e.g., Mycobacterium tuberculosis), relying on oxidative phosphorylation for ATP synthesis, whereas others are strict anaerobes (e.g., Clostridioides difficile) relying primarily on substrate-level phosphorylation using various fermentative pathways. Yet other species, such as Staphylococcus aureus and Escherichia coli are facultative anaerobes and can convert energy via both respiratory and fermentative pathways. The metabolic propensity and growth conditions experienced by bacterial species have a great impact on the necessity of a functional ATP synthase for viability.The ATP synthase has been validated as a druggable target with the approval of the ATP synthase inhibitor bedaquiline for treatment of M. tuberculosis, an organism in which the ATP synthase is essential for growth. Currently, no ATP synthase inhibitors are in clinical use against non-mycobacterial pathogens.In this review, the physiological functions of the ATP synthase in various bacterial pathogens are discussed in relation to the metabolic pathways utilized for providing energy. The ATP synthase is essential in important pathogenic species that are obligate aerobes, obligate anaerobes and aerotolerant anaerobes, whereas it is dispensable for growth in most facultative anaerobic pathogens. Interference with the ATP synthase in facultative anaerobes has physiological consequences, such as membrane hyperpolarization, which can be exploited for combination therapies.Collectively, the available data indicate that the ATP synthase is an interesting target for development of new antimicrobials beyond M. tuberculosis.